Parkinson’s in Farmers, Could it be Caused by the Paraquat Herbicide Exposure? - Arriz Akbar Sukadi; Dewi Yunia Fitriani; Levina Chandra Khoe (The Indonesian Journal of Community and Occupational Medicine, 2022)
Many studies have been carried out to assess the safety of the widespread use of pesticides in agriculture with diseases in farmers. A 52-year-old female farmer suffered Parkinson’s after working 27 years using paraquat herbicide. This study was conducted to obtain answers about the impact of paraquat exposure on the incidence of Parkinson’s in farmers through evidence-based case reports (EBCR) derived from a literature review.The review was conducted through the search and selection method of articles in PubMed, ProQuest, and Cochrane Library to answer research questions. The article search process used the keywords “paraquat AND Parkinson AND farmer”. Article selection was carried out using predetermined inclusion and exclusion criteria. In the initial search, 35 articles were retrieved and through the selection process three articles of the meta-analysis systematic review were selected.Selected articles from Tangamornsuksan and Vaccari show a statistically significant association between paraquat exposure and the incidence of Parkinson’s disease (PD) in workers, with a pooled OR of 1.70 and 1.24. Meanwhile, Yan’s study shows that duration of exposure to pesticides increases the risk of PD. The result showed a 5 and 10 years of duration exposure to pesticide were associated with a 5% and 11% augment in the risk of PD. All studies applied validation to reduce bias and heterogeneity effects or inadequate statistical methods.Based on the results of this evidence-based case report, it shows that the epidemiological studies taken can prove the possibility that Parkinson’s disease in this farmer is caused by exposure to paraquat.